Persepsi Guru PAI Terhadap Kurikulum Merdeka Belajar di SMPN 4 Kendari - Siti Rodiah; Moh. Yahya Obaid; Jumarddin La Fua (Tarbiyatul Akhyar: Jurnal Pendidikan, 2025)
This study aims to understand Islamic Education (PAI) teachers' perceptions of the implementation of the Merdeka Belajar curriculum at SMP Negeri 4 Kendari. It examines the teachers' understanding of the curriculum's implementation, their perceptions of its application, and how the curriculum is implemented in Islamic Education subjects. The research employs a descriptive qualitative approach. Data were collected through observation, interviews, and documentation. The data analysis technique used includes data reduction, data presentation, and drawing conclusions.  The results of the study show that: (1) Islamic Education teachers have a good understanding of the implementation of the Merdeka Belajar curriculum, including its concepts, objectives, innovative teaching practices, and the integration of technology in learning. (2) Islamic Education teachers have a positive perception (views, responses, and evaluations) of the curriculum's implementation, as it simplifies the teaching process, enhances students' motivation, and better addresses students' needs. (3) The planning of the Merdeka Belajar curriculum for Islamic Education subjects has been effectively implemented, beginning with the analysis of learning outcomes and the preparation of teaching modules. (4) The implementation of Islamic Education teaching aligns with the pre-designed teaching tools. (5) Assessment in Islamic Education is conducted through three types of evaluations: diagnostic, formative, and summative.Thus, this study contributes new insights by highlighting innovative approaches in Islamic Education teaching in the era of the Merdeka Belajar curriculum. The findings reveal how technology integration and the application of innovative teaching methods can enhance teaching efficiency and the relevance of learning to meet students' needs in the digital age.